2015
DOI: 10.1002/2014wr015348
|View full text |Cite
|
Sign up to set email alerts
|

The influence of multiyear drought on the annual rainfall‐runoff relationship: AnAustralian perspective

Abstract: Most current long-term (decadal and longer) hydrological predictions implicitly assume that hydrological processes are stationary even under changing climate. However, in practice, we suspect that changing climatic conditions may affect runoff generation processes and cause changes in the rainfallrunoff relationship. In this article, we investigate whether temporary but prolonged (i.e., of the order of a decade) shifts in rainfall result in changes in rainfall-runoff relationships at the catchment scale. Annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
282
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 214 publications
(304 citation statements)
references
References 80 publications
21
282
0
1
Order By: Relevance
“…-2009(ca. , Cai et al, 2014Saft et al, 2015). The winter rainfall deficit during the socalled Millennium Drought caused major water crises, affecting river ecosystems and agricultural production as reviewed in van Dijk et al (2013).…”
Section: Megadrought In Central Chilementioning
confidence: 99%
“…-2009(ca. , Cai et al, 2014Saft et al, 2015). The winter rainfall deficit during the socalled Millennium Drought caused major water crises, affecting river ecosystems and agricultural production as reviewed in van Dijk et al (2013).…”
Section: Megadrought In Central Chilementioning
confidence: 99%
“…In the 15 times dry events under the regression line in the case of the total regression, there are 9 times significant change in the PRR (p < 0.05), accounting for about 60% of the total situation. This means that sustained drought results in lowered runoff generation rates for similar precipitation amounts (Saft et al, 2015). Thus in a continued years with decreased precipitation, we can conclude that lower runoff not only relate to the lower precipitation, but also less runoff than expected caused by the multi_yeat 5 drought period.…”
Section: Variability Of the Prr During Dry Period In Each Watershedmentioning
confidence: 68%
“…There are two main forms of the response of the PRR to multi-year droughts: no significant change and downward significant change. Saft et al (2015) have shown that there was also a significant upward trend in the PRR during a drought period in southeastern Australian watersheds, but the probability of 20 such events is small. It is also not clear whether the phenomenon is real or just sampling fluctuations.…”
Section: The Influence Of Multi-year Drought On the Ecosystem Servicementioning
confidence: 97%
See 2 more Smart Citations